Benign lymphoepithelial cyst (Bangladesh Journal of Otorhinolaryngology, 2010)
Benign lymphoepithelial cyst, also known, as branchial cyst is an infrequent lesion usuallyoccurs in the parotid gland or the lateral cervical area including lymph nodes. It occurs due tothe process of lymphocyte-induced cystic ductular dilatation and is always diagnosedpostoperatively by histopathological examination. The cyst is usually lined by squamousepithelium surrounded by lymphoid stroma. Although unusual, two cases diagnosed withintwo months are reported here. Both patients were male but the locations of the lesions weredifferent. One lesion was within cervical lymph node and the other was near the parotid gland.Both the lesions were surgically excised and diagnosed histopathologically as benignlymphoepithelial cyst. Its frequent association with HIV infected patients since last two decadeshas made it a significant lesion now-a-days. In this regard along with reported two cases briefliterature reviews including origin, diagnosis and treatment are discussed.Key words: Benign lymphoepithelial cyst; parotid; lymph node; HIV infected patients.DOI: 10.3329/bjo.v16i1.5783Bangladesh J Otorhinolaryngol 2010; 16(1): 60-65